2010
DOI: 10.1007/s10562-010-0494-x
|View full text |Cite
|
Sign up to set email alerts
|

An Easy Route to Synthesize Novel Mesostructured Silicas Al/SBA-16 and Its Catalytic Application

Abstract: Al-containing SBA-16 (with different Si/Al molar ratios) was prepared by an easy post-grafting method using F127 as structure-directing agent and aluminum isopropoxide as Al source. The structure of the solid catalyst was fully characterized by X-ray diffraction (XRD) analysis, N 2 adsorption, scanning electron micrographs (SEM), transmission electron micrographs (TEM) and 27 Al MAS NMR. The results indicated that the materials possess three-dimension caged-like mesostructure and Al was successfully incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The very broad diffraction peak at a 2y of around 251 is typical reflection of amorphous silica. 22 The diffraction peak assigned to metallic Ru (JCPDS 00-006-0663) at a 2y of around 441 is observed for all supported catalysts. 21 27 Al MAS NMR spectra of the supports are shown in Fig.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 88%
“…The very broad diffraction peak at a 2y of around 251 is typical reflection of amorphous silica. 22 The diffraction peak assigned to metallic Ru (JCPDS 00-006-0663) at a 2y of around 441 is observed for all supported catalysts. 21 27 Al MAS NMR spectra of the supports are shown in Fig.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 88%
“…The very broad diffraction peaks at 2θ around 23°a re characteristics of amorphous silica. 22 The absence of alumina reflections in Al-SBA-15 with lower Al/Si ratio (0.2, 0.5) suggests that the aluminum is homogeneously dispersed in the structure of Al-SBA-15. 19 While in Al(1.0), a broad peak at 67°is observed, indicating the formation of γ-Al 2 O 3 by Al species without incorporation into the framework.…”
Section: Resultsmentioning
confidence: 95%
“…Py-IR spectra of NiMo/​AS- x are shown in Figure . The peaks related to the physisorbed pyridine at 1444 and 1595 cm –1 cannot be observed after degassing at 200 and 350 °C, demonstrating that pyridine chemisorbed on the surface of NiMo/​AS- x catalysts . The peaks at about 1640 and 1540 cm –1 should be assigned to Brönsted acid sites.…”
Section: Resultsmentioning
confidence: 96%
“…The authors attributed the reason to the contribution of high dispersion states of Mo active species . A postgrafting method to synthesize Al-SBA-16 materials has been reported by Ma et al . Moreover, the effect of Si and Al molar ratios on the catalytic performances of phenol tert -butylation reaction showed that Al-SBA-16 performed a much higher catalytic activity than the mesoporous Al-SBA-15 material, which should be ascribed to that Al-SBA-16 materials with cagelike mesostructures provided high accessibility to the reactant molecules.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation